Analysis of FOXP3 regulatory T cell subpopulations in peripheral blood and tissue of patients with systemic lupus erythematosus - Schmidt, Angelika; Venigalla, Ram Kumar Chowdary; Max, Regina; Lorenz, Hanns-Martin; Gröne, Hermann-Josef; Krammer, Peter H. (Immunologic research, 2017)
Regulatory T cells (Tregs) are critical mediators of immune tolerance, yet their involvement in the autoimmune disease systemic lupus erythematosus (SLE) is incompletely understood. We analyzed CD4+ T cell subpopulations with Treg-related phenotypes and their association with disease activity in peripheral blood (PB) and tissues of patients with SLE. In detail, we quantified subpopulations regarding CD25, FOXP3, CD62L, CCR6, CD27, CD45RA, and CD45RO expression in PB from 31 patients with SLE divided into two disease activity groups and 32 healthy controls using flow cytometry. CD4+ and FOXP3+ T cells in skin and kidney biopsies of patients with SLE were quantified by immunohistochemistry. CD4+CD25+/++FOXP3+ and CD4+CD25+CD45RA−/CD45RO+ T cell frequencies were significantly higher in PB from patients with active compared to inactive SLE. The fraction of CD4+CD25++FOXP3+ Tregs and CD4+CD25+CD45RA+/CD45RO− naïve Tregs was not significantly different between these groups. CD4+CD25++ Tregs from active SLE patients comprised significantly less CD27+ cells and more CCR6+ cells compared to patients with inactive SLE. The percentage of CD4+FOXP3+ T cells among inflammatory infiltrates in skin and kidney biopsies of SLE patients was not different from other inflammatory skin/kidney diseases. In conclusion, although CD4+FOXP3+ T cell frequencies in the inflamed tissues of SLE patients were comparable to other inflammatory diseases, distinct T cell subpopulations appeared misbalanced in PB of patients with active SLE. Here, cells phenotypically resembling activated T cells, but not Tregs, were increased compared to patients with inactive SLE. Within Tregs of patients with active SLE, markers related to Treg function and homing were altered.